Problems and Prospects of Privatisation Of Library and Information Services in India: The Information Industry View Point - Sathyanarayana, N.V. (DESIDOC Journal of Library & Information Technology, 2002)
The author explains the concept of privatisation and the changing library culture of charging a fee for the service with reference to independent- Iibraries and libraries that are part of a bigger parent organisation. It discusses possibilities like partnership between libraries and industries for effective marketing and distribution support and the problems that may crop up in suck a partnership. http://dx.doi.org/10.14429/dbit.15.5.3196